Nursing for wellness in older adults - Miller, Carol A. (Philadelphia : Wolters Kluwer, 2019)
Ensure the most effective wellness-oriented nursing care for older adults--in any healthcare setting. Confidently deliver wellness-oriented care for older adults across a changing healthcare environment with the latest evidence-based coverage of gerontological nursing. Comprehensively revised and updated, Nursing for Wellness in Older Adults, Eighth Edition fosters your understanding of both the physiologic and psychosocial aspects of aging, as well as broader issues of cultural competence, legal matters, and ethical concerns. Organized around the author's proven Functional Consequences Theory for Promoting Wellness in Older Adults, this trusted text focuses on equipping you to work proactively with older adults to promote high levels of functioning and quality of life, despite the limitations associated with aging, disease, and related conditions. Technology to Promote Wellness in Older Adults boxes familiarize you with technology-based interventions for promoting wellness in older adults. Interprofessional Collaboration (IPC) coverage emphasizes strategies for working with other healthcare professionals in managing care of older patients. Global Perspective boxes illustrate proven international approaches to quality gerontological nursing. Unfolding Patient Stories authored by the National League for Nursing challenge you to apply your understanding to realistic patient scenarios. A Transitional Care Unfolding Case Study helps you manage a patient requiring care across a variety of healthcare settings. Case Studies (both multipart and standalone) encourage you to apply nursing theory to real-life situations. Quality and Safety Education in Nursing (QSEN) examples help you apply knowledge and skills to care plans for unfolding cases. Assessment, Intervention, Evidence-Based Practice, Cultural Considerations, Diversity Note, and Caregiver Wellness boxes detail helpful approaches and tools for effective wellness-oriented nursing practice. Online Learning Activities point readers to the book's companion web page to access related resources, articles, and evidence-based guidelines.
Part 1. Older adults and wellness. Seeing older adults through the eyes of wellness -- Addressing diversity of older adults -- Applying a nursing model for promoting wellness in older adults -- Theoretical perspectives on aging well -- Part 2. Nursing considerations for older adults. Gerontological nursing and health promotion -- Health care for older adults in various settings -- Assessment of health and functioning -- Medications and other bioactive substances -- Legal and ethical concerns -- Elder abuse and neglect -- Part 3. Promoting wellness in psychosocial function. Cognitive wellness -- Psychosocial wellness -- Psychosocial assessment -- Impaired cognitive function : delirium and dementia -- Impaired affective function : depression -- Part 4. Promoting wellness in physical function. Hearing -- Vision -- Digestion and nutrition -- Urinary function -- Cardiovascular function -- Respiratory function -- Safe mobility -- Integumentary function -- Sleep and rest -- Thermoregulation -- Sexual function -- Part 5. Promoting wellness during illness and transitions in care. Caring for older adults during illness -- Caring for older adults experiencing pain -- Caring for older adults at the end of life.
Includes bibliographical references and index.
Keywords: Geriatric nursing; Older people -- Psychology; Health promotion; Nursing theory